Oral health indicators in the Interfederative Pacts of the Unified Health System: development in the 1998-2016 period - Mary Anne de Souza Alves FRANÇA; Maria do Carmo Matias FREIRE; Edsaura Maria PEREIRA; Vânia Cristina MARCELO (Universidade Estadual Paulista, 2018)
Abstract Introduction In recent decades, the Ministry of Health has been recommending the use of indicators for the assessment and monitoring of health care. Over the years, it has instituted interfederative pacts dealing with health indicators, including oral health indicators, with the purpose of encouraging health system managers to incorporate the monitoring and assessment of actions in their practice, as well as enabling the follow-up of the performance of services. Objective To analyze the development of oral health indicators propounded in the interfederative pacts of the Unified Health System (SUS) in Brazil between 1998 and 2016. Material and method Documentary research based on government guidelines issued during the analyzed period. The variables studied were the characteristics of publications and indicators (denomination, method of calculation, source and purposes). Result In the period of 1998-2016, oral health indicators were proposed in the pact on primary care indicators (1998-2006), in the Pacts for Health (2007-2011), and in the resolutions of the tripartite intermanagerial committee (2012, 2013 and 2016). Changes were identified over this period, characterized by the inclusion and exclusion of indicators, and by a drastic reduction in the number of indicators, eventually leading to only one retained indicator: "Proportion of tooth extractions in relation to procedures." Conclusion There were changes in oral health indicators over the analyzed period, characterized by periods of advancement and regression, eventually resulting in a single indicator related to mutilating actions (tooth extractions), effective in 2016.